Controlling Cellular Uptake of Nanoparticles with pH-Sensitive Polymers - Ding, Hong-ming (Nature Publishing Group, 2013)
The major challenge in cancer therapy is to efficiently translocate drug molecules into cancer tumors without doing any damage to healthy tissues. Since there exist pH gradients between tumor and normal tissues, pH-sensitive materials may have great potential to overcome such challenge. Here, we report one new type of pH-responsive drug delivery system where pH-sensitive polymers are introduced to control the cellular uptake of nanoparticles under different pH environments through dissipative particle dynamics simulations. Interestingly, the behavior of cellular uptake of nanoparticles here exhibits “smart” pH-responsive properties: for lower and higher pH, the nanoparticles can be taken up by cell membranes, while for pH in middle range, the endocytosis is blocked. Further, it is found that receptor-ligand interactions as well as surface charge property of nanoparticles and membranes can also have important impacts on the endocytosis. The present study may give some significant insights into future stimulus-responsive medical materials design.